Abdurrahman Wahid (Telaah Atas Ide Neo-Modernisme) - Barsihannor Barsihannor (Jurnal Adabiyah: Humanities and Islamic Studies, 2011)
Abdurrahman Wahid, as stated by Greg Berton was a new modern thinker of modern Islam who pionered the Islamic movement based on cultural genuine. He who was popularly called Gusdur has ever become the president of Indonesia and abolished a number of racial desrcimination. According to him, Islam highly appreciates the difference among human being, as a part of sunnatullah. In his opinion, two schools of Islamic movement such as progressivism and traditionalism must be mixed in a good harmony.